DNA‐Mediated Morphological Control of Silver Nanoparticles. Issue 39 (23rd August 2016) - Li, Jiuxing; Zhu, Zhi; Liu, Fang; Zhu, Bingqing; Ma, Yanli; Yan, Jinmao; Lin, Bingqian; Ke, Guoliang; Liu, Rudi; Zhou, Leiji; Tu, Song; Yang, Chaoyong
Abstract : It is demonstrated that DNA can be used to control the synthesis of silver nanoplates with different morphologies using spherical silver seeds. UV–vis spectroscopy, transmission electron microscopy, scanning electron microscopy, X‐ray photoelectron spectroscopy, and Raman spectroscopy are used to characterize the synthesized nanoparticles. Silver nanoprisms are encoded by poly C and poly G, while silver flower bouquets and silver nanodiscs are synthesized using poly A and poly T, respectively. The length of DNA is found to have little effect on the morphology of silver nanoparticles. Moreover, the synthesized silver nanoplates are found to have high surface enhanced Raman scattering enhancement ability, good antibacterial activity, and good biocompatibility. These discoveries will broaden the application of DNA in nanoscience and will provide a new platform to investigate the interaction between DNA sequences and silver nanoparticles. Abstract : Morphological control synthesis of silver nanoparticles is implemented by DNA of different sequences. Silver nanoprisms (AgNPRs) could be synthesized by DNA composed of C or G bases, while DNA composed of A or T bases were able to control the synthesis of silver nanoflowers or silver nanodiscs, respectively.